Respuesta :

9514 1404 393

Answer:

   B.  √6

Step-by-step explanation:

The circles are not tangent to one another. If they were, the distance between their centers would be the sum of their radii: 1 +1 = 2.

__

The center of the first circle is (√3, √3), and the center of the second is the origin. The distance between these two centers is given by the distance formula:

  d = √((x2 -x1)^2 +(y2 -y1)^2)

  d = √((√3 -0)^2 +(√3 -0)^2) = √(3+3) = √6 . . . . matches choice B

Ver imagen sqdancefan